Sustainability, Stability, and Growth: A Time Series Analysis of Tourism Drivers in Thailand - Hechmi, Soumaya (Journal of Ecohumanism, 2025)
This study examines the dynamic effects of renewable energy consumption, economic growth (GDP), and geopolitical risk (GPR) on tourism in Thailand during the period 1995-2023. Utilizing rigorous time series econometric techniques, including cointegration analysis and error correction modeling, the study examines both the short-run and long-run relationships between the selected macroeconomic variables and tourism development. The findings confirm that GDP and renewable energy both exert positive and statistically significant influences on tourism in the short and long term, mirroring economic strength and sustainability in driving tourism performance. The geopolitical risk, however, significantly negatively affects tourism in the long term, inferring that political instability and conflict in the region in the long term can ruin Thailand’s image as a destination for tourists. These results emphasize the importance of sustainable energy investment, macroeconomic stability, and effective geopolitical risk management in supporting the growth and resilience of Thailand’s tourism sector. The study offers valuable policy recommendations to create a secure, green, and economically prosperous tourism sector in Thailand.